1995
DOI: 10.1074/jbc.270.35.20724
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Regulation of a Novel DNA Binding Complex in Saccharomyces cerevisiae with E2F-like Properties

Abstract: Using a biochemical approach, we have detected an activity in Saccharomyces cerevisiae extract that displays the same DNA binding specificity as the mammalian E2F transcription factor and interacts with TTTCGCGC promoter elements. Additional studies revealed that this factor, termed SCELA (S. cerevisiae E2F-like activity), also binds to the closely related SCB promoter sequences. SCB sites (consensus: TTTCGTG) are involved in the cell cycle regulation of several S. cerevisiae cyclin genes and have been shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Indeed, it was previously shown that Clb2p degradation is essential for exit from mitosis (Surana et al ., 1993), and disappearance of Clb2p would be a good indication that sun4 Δ uth1 Δ cells finish their cell cycle normally. Proteins were extracted from the samples obtained after elutriation and probed with an anti‐Clb2p antibody as well as one against Swi6p, a constitutive transcriptional factor (Vemu and Reichel, 1995) which we used here as a loading control. In accordance with the results obtained with wild‐type strain (Schwob et al ., 1994; Schwab et al ., 1997), Clb2p, which was absent in the elutriated sun4 Δ uth1 Δ cells, appeared at 90 min when cells entered G 2 and peaked around 120 min, at the time most cells have undergone mitosis (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it was previously shown that Clb2p degradation is essential for exit from mitosis (Surana et al ., 1993), and disappearance of Clb2p would be a good indication that sun4 Δ uth1 Δ cells finish their cell cycle normally. Proteins were extracted from the samples obtained after elutriation and probed with an anti‐Clb2p antibody as well as one against Swi6p, a constitutive transcriptional factor (Vemu and Reichel, 1995) which we used here as a loading control. In accordance with the results obtained with wild‐type strain (Schwob et al ., 1994; Schwab et al ., 1997), Clb2p, which was absent in the elutriated sun4 Δ uth1 Δ cells, appeared at 90 min when cells entered G 2 and peaked around 120 min, at the time most cells have undergone mitosis (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…The Cln3–Cdc28 kinase could serve a similar function to move cells through G 1 , the rate of this process determining G 1 length. Whether such a system exists in yeast remains to be seen; however, it is worth noting that an E2F‐like activity (termed SCELA) has been identified in yeast (Vemu and Reichel, 1995). As is the case with E2F, SCELA binds to elements that regulate the expression of the downstream cyclins, in this case CLN1 and CLN2 .…”
Section: Discussionmentioning
confidence: 99%
“…Band shift assays using purified proteins or in vitro translation products suggest that Swi4 and Mbp1 provide the primary DNA recognition function and that Swi6 enhances the affinity of the complex for its target (10, 12, 13). More recently, another complex that binds SCBs but does not contain Swi6 or Swi4 has been reported (14).…”
Section: Mlu1 Cell Cycle Boxes or Mcbsmentioning
confidence: 99%